The Relationship between Jigsaw Cooperative Learning Method and Parents Attention with English Learning Achievement Student in Public Junior High School 4 Bogor - Kartika, Ika; Saepudin, Saepudin (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This study aims to prove and examine the relationship between parents attention to English learning achievement, either individually or together. The hypotheses tested were: (1) there is a positive the relationship between the jigsaw cooperative learning method and English learning achievement, (2) there was a positive the relationship between parents attention and English learning achievement, and (3) there was a positive the relationship between jigsaw cooperative learning method and parents attention together towards the English learning achievement. The research method used is survey method with correlational approach. The research was conducted at Public Junior High School 4 Bogor. The study respondents were 80 students, with the sampling technique using is cluster random sampling technique. The instrument uses the English learning achievement test questionnaire as the dependent variable, while the model instrument is corporative jigsaw method and the attention of the parent as independent variable. The result of the research shows that: (1) there is positive the relationship between model of jigsaw method to English learning achievement; (2) there is positive the relationship between parents attention to English learning achievement; (3) there are a positive the relationship between the jigsaw cooperative learning method and the parents attention collectively to the English learning achievement. Thus the results of this study conclude that English learning achievement can be improved through improved jigsaw cooperative learning method and parental attention.